微波预处理对芝麻油中芝麻木酚素含量 及油脂品质的影响 Effects of microwave pretreatment on the sesame lignan content and quality of sesame oil - 盛冰莹1，陈振伟2，张晨霞1，马宇翔1，汪学德1，郑永战1，3 SHENG Bingying1, CHEN Zhenwei2, ZHANG Chenxia1, MA Yuxiang1, WANG Xuede1, ZHENG Yongzhan1，3 (Zhongguo youzhi, 2023)
为了确定高芝麻酚芝麻油的最适微波预处理条件，将芝麻水分含量调节为5个梯度，在不同微波预处理时间下制得芝麻油样品，对其芝麻木酚素含量、酸值、茴香胺值、氧化诱导时间、脂肪酸组成、生育酚含量、有害物质（多环芳烃和杂环胺）含量及感官品质进行了分析，探究芝麻水分含量和微波预处理时间对芝麻油中芝麻木酚素含量及油脂品质的影响。结果表明：微波预处理时间6 min、芝麻水分含量7%条件下制得的芝麻油芝麻酚含量较高，芝麻油酸值符合国家标准限定要求，氧化稳定性较强，有害物质杂环胺和多环芳烃含量处于适当的可控水平，同时兼顾了芝麻油的固有风味，消费者的喜爱度较高。综上，高芝麻酚芝麻油的最适微波预处理条件为微波预处理时间6 min，芝麻水分含量7%。To determine the optimal conditions of microwave pretreatment for sesamol-riched sesame oils, the moisture content of sesame seeds was adjusted to five gradients and sesame oil samples were produced under different microwave pretreatment time, and the sesame lignan content, acid value, anisidine value, oxidation induction time, fatty acid composition, tocopherol content, harmful substances (heterocyclic amines and polycyclic aromatic hydrocarbons) content and sensory quality of the oil were analyzed to investigate the effects of sesame seed moisture content and microwave pretreatment time on the sesame lignan content and quality of sesame oil. The results showed that when the microwave time was 6 min and the moisture content of sesame seeds was 7%, the sesame oil produced had a high sesamol content, its acid value met the limited requirements of the national standards, the oxidative stability was strong, and the content of harmful substances including heterocyclic amines and polycyclic aromatic hydrocarbons was at an appropriate and controllable level. In addition, taking into account the inherent flavor of sesame oil, it was highly accepted by consumers. In summary, the optimal microwave pretreatment conditions for high sesamol sesame oil are microwave time 6 min and moisture content of sesame seeds 7%.